Prevalence and cause of gestational diabetes mellitus in a tertiary care center in Kolar district: a population based study - Tummala, Poojita; M., Munikrishna; P., Kiranmayee (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Gestational diabetes mellitus (GDM) is carbohydrate intolerance at the onset of pregnancy which induces pathological short term or long term outcomes for both mother and baby. The aim of the present study was to know the prevalence of GDM in pregnant women who were attending the antenatal care (ANC) center at a tertiary care hospital in Kolar, Karnataka, India. Methods: This prospective study was conducted in Department of Obstetrics and Gynecology, Sri Devaraj Urs Medical College, a constituent of Sri Devaraj Urs Academy of Higher Education and Research, Kolar, Karnataka, India. The duration of the study was two months. In this study, 108 pregnant women above 24 weeks of gestation were screened for GDM by oral glucose tolerance test. Fasting 2 milli liter blood was collected and were given 75 grams of glucose in 200 milli liters of water and asked to drink within 5 minutes. Again 2 milli liters venous blood was collected after 1 hour and 2 hours from all participants. Plasma sample was used for the estimation of glucose by glucose oxidase and peroxidase (GOD-POD) method. Results: Out of 108, 12 women (11.1%) were diagnosed with GDM. The prevalence rate was higher in the age group of 26-30 years (41.6%). Among 12 diabetic women, five (47.2%) exercised regularly and seven (58.3%) did not doing exercise. Out of 12 GDM subjects, eight of them had family history of diabetes in first degree relatives; among which one was hypertensive and five were suffering from thyroid problems. Conclusions: In the present study, the prevalence of GDM was found to be 11.1%. Prevalence of GDM might be influenced by increasing age, pre pregnancy weight, family history of diabetes, past history of pregnancy complications, status of literacy and exercise.